Evaluación de los procedimientos de diagnóstico de la fiebre tifoidea - Gotuzzo, Eduardo (1978)
Plate agglutinations, serial blood cultures and single bone marrow aspirate cultures were evaluated as to their efficiency for diagnosis of typhoid fever in 60 patients, most of whom had received previous antibacterial treatment. Plate agglutination was "positive" in 25% of the patients at hospitalization, the proportion later increasing to 56.6%. Salmonella typhi was isolated in 95% of bone marrow cultures, while only 43.3% of the patients had at least one positive blood culture. the effectiveness of blood and bone marrow cultures wa similar whether they were performed using Trypticase Soy Broth or using a biphasic Trypticase Soy Broth/Trypticase Soy Agar Reuiz Castañeda - type bottle.   The diasnostic would have been missed in 13 patients (21.7%) if it had rested on plate agglutination and blood culture alone. Bone marrow culture provides a faster bacterial growth and improved yield in any period of typhoid fever, including patients who had received antibacterial theatment. The sensitivity of bone marrow culture was statistically superior to the other diagnostic procedures evaluated.